Acquiescence and Dogmatism: Impact and relations across two different item formats. (September 2016) - Ferrando, Pere J.; Morales-Vives, Fabia; Lorenzo-Seva, Urbano
Abstract: The literature suggests that (a) responses to typical Dogmatism items are non-negligibly impacted by acquiescent responding, and (b) the dimension of Dogmatism is related to Acquiescence conceptualized as an individual-differences variable. In this article we first rigorously assessed these two basic hypotheses by using a recently developed confirmatory factor-analytic model. Second, we assessed the extent to which the impact and relations were consistent across a binary format and a graded format. Finally, the convergent validity of the Acquiescence scores across the two formats was assessed. In both datasets the Dogmatism items were found to be impacted by Acquiescence, and the relation Acquiescence-Dogmatism was strong in the expected direction. Furthermore, the Acquiescence scores were very consistent across the two different formats. The theoretical implications of the results and future lines of research are discussed. Highlights: Dogmatism items are impacted by Acquiescence bias. The more dogmatic respondents tend to show greater acquiescence scores. There is a consistency in the effect of Acquiescence across time and response formats. The Acquiescence and Dogmatism relation is very similar in both response formats. Acquiescence can be assessed and controlled with the procedure used in this study.